Retorika Dakwah Ustad Syukri Albani di Media Sosial Tiktok - Rozi, Fahrur; Azhar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
First of all, technology is developing a number of advanced, convenient features at an ever-increasing pace. In this era of digitalization, many human tasks can be completed in a short time. Like Islamic preaching, Islam as Rahmatan Lil Alamin's religion must of course be adaptive and inclusive in facing the forces of globalization. The Tiktok application is one of several new media being produced, taken for granted by Indonesian society, and has both beneficial and detrimental impacts. The millennial generation, which is prone to anxiety about the uniformity of modernization, is starting to feel the negative impact of Tiktok, a new media platform that provides entertainment, education and information. Ustad Syukri Albani, one of the preachers, added further meaning to this application. This research examines how preacher Ustad Syukri Albani formulates his preaching strategy on social media Tiktok and how he uses da'wah rhetoric as the main means of conveying his preaching there. This is achieved by combining content analysis studies with qualitative research methodology. Research shows that Ustad Syukri Albani's preaching rhetoric which can be seen on social media is one of the main variables that determines how individuals behave in accordance with Islamic principles.